Implications of heterogeneous fracture distribution on reservoir quality; an analogue from the Torridon Group sandstone, Moine Thrust Belt, NW Scotland. (March 2018) - Watkins, Hannah; Healy, David; Bond, Clare E.; Butler, Robert W.H.
Abstract: Understanding fracture network variation is fundamental in characterising fractured reservoirs. Simple relationships between fractures, stress and strain are commonly assumed in fold-thrust structures, inferring relatively homogeneous fracture patterns. In reality fractures are more complex, commonly appearing as heterogeneous networks at outcrop. We use the Achnashellach Culmination (NW Scotland) as an outcrop analogue to a folded tight sandstone reservoir in a thrust belt. We present fracture data is collected from four fold-thrust structures to determine how fracture connectivity, orientation, permeability anisotropy and fill vary at different structural positions. We use a 3D model of the field area, constructed using field observations and bedding data, and geomechanically restored using Move software, to determine how factors such as fold curvature and strain influence fracture variation. Fracture patterns in the Torridon Group are consistent and predictable in high strain forelimbs, however in low strain backlimbs fracture patterns are inconsistent. Heterogeneities in fracture connectivity and orientation in low strain regions do not correspond to fluctuations in strain or fold curvature. We infer that where strain is low, other factors such as lithology have a greater control on fracture formation. Despite unpredictable fracture attributes in low strain regions, fractured reservoir quality would be highest here because fractures in high strain forelimbs are infilled with quartz. Heterogeneities in fracture attribute data on fold backlimbs mean that fractured reservoir quality and reservoir potential is difficult to predict. Highlights: Fracture attribute data is collected from a fold-thrust outcrop analogue. A 3D model is built and restored to determine structural controls on fracturing. Fractured reservoir quality is low in high strain regions due to mineral-fill. Fractures are open in low strain regions giving higher reservoir potential. Variable connectivity in low strain zones means reservoir quality is unpredictable.